Electron scale structures and magnetic reconnection signatures in the turbulent magnetosheath - E. Yordanova; Z. Vörös; A. Varsani; D. B. Graham; C. Norgren; Yu. V. Khotyaintsev; A. Vaivads; E. Eriksson; R. Nakamura; P.‐A. Lindqvist; G. Marklund; R. E. Ergun; et al. (Geophysical Research Letters)
Abstract Collisionless space plasma turbulence can generate reconnecting thin current sheets as suggested by recent results of numerical magnetohydrodynamic simulations. The Magnetospheric Multiscale (MMS) mission provides the first serious opportunity to verify whether small ion‐electron‐scale reconnection, generated by turbulence, resembles the reconnection events frequently observed in the magnetotail or at the magnetopause. Here we investigate field and particle observations obtained by the MMS fleet in the turbulent terrestrial magnetosheath behind quasi‐parallel bow shock geometry. We observe multiple small‐scale current sheets during the event and present a detailed look of one of the detected structures. The emergence of thin current sheets can lead to electron scale structures. Within these structures, we see signatures of ion demagnetization, electron jets, electron heating, and agyrotropy suggesting that MMS spacecraft observe reconnection at these scales.